Internal Aspects in their Impact on the Quality of Financial Reports of Gianyar Village Credit Institutions (LPD) - Sagung Oka Pradnyawati; Putu Kepramareni; Ni Putu Indah Kusumawati; Luh Gde Pasek Puspa Dewi (AIBPM Publisher, 2024)
There is no other region that has the Village Credit Institution (LPD), a financial institution run by traditional villages, except Bali. The sustainability of LPDs needs to be maintained. Indicators for assessing the health of LPDs can be through financial reports submitted to supervisory institutions in each district/city. Two of the forty LPDs in the Gianyar sub-district (2021) do not submit reports, and many reports do not meet user needs; this is also a common occurrence in other locations. The author raises this issue to be researched from the LPD's internal side, such as understanding accounting, supervisory bodies, use of information technology, leader ethics and HR competency. The questionnaire is completed by all parties involved in the preparation of financial reports, and the author gathers data directly. Researchers tested and found a positive relationship between the use of information technology, leader ethics and HR competency on the quality of the financial reports produced. However, understanding of accounting and regulatory bodies does not show a significant influence.